Assessment of static and dynamic balance in overweight and obese children with and without flatfoot: A cross-sectional study - Pallavi Sharma; Deepa Metgud (Indian Journal of Health Sciences and Biomedical Research KLEU, 2017)
Background: Childhood obesity and overweight have been referred by health organization as serious epidemic and global problems that are on the rise. The consequence of being overweight in children is the greater impairment of mobility which may result in several orthopedic conditions. The foot dimensions of overweight children and obese children will be larger than those of normal weight children. Balance is defined as an ability to maintain the center of mass over base of support. Balance as a sensorimotor ability helps in maintaining static and dynamic equilibrium. The presence of abnormalities in the foot structures may affect the displacement of the body, function in static, and dynamic position. Methodology: This was a cross-sectional study done in overweight and obese children with and without flatfoot. A total of 1165 children were screened out of which 87 were found to have obesity between the age group of 6–12 years from 11 schools. Static balance of children was measured using balance error scoring system (BESS) and stork balance stand test (SBST), and dynamic balance was measured using four square step test (FSST) and modified bass test of dynamic balance (MBTDB). Results: The static balance was significantly affected in obese children with and without flatfoot and also in overweight children with flatfoot whereas dynamic balance was affected in obese children with flatfoot. BESS (P = 0.001), MBTDB (P = 0.006), and FSST (P = 0.001) were statistically significant. There was no significant difference found on SBST (P = 0.0657) when compared within and between the groups. Conclusion: Obese children with flatfoot had poor static and dynamic balance compared to overweight children with flatfoot when it was tested on BESS and MBTDB and FSST.